Nitric Oxide-Induced Polycystic Ovaries in The Wistar Rat - Hassani, Fatemeh (Int J Fertil Steril, 2012)
BACKGROUND: Nitric oxide (NO) involves in polycystic ovary syndrome (PCOS), a cause of infertility in women during the reproductive age. The PCOS is now categorized as an inflammatory phenomenon. The aim of this study was to evaluate the role of NO, a proinflammatory agent, in this syndrome at histological and biochemical levels. MATERIALS AND METHODS: In this experimental study, animals were female Wistar rats (weighing 200-250 g) kept under standard conditions. L-Arginine (50-200 mg/kg), a precursor of NO, was injected intra-peritoneally (i.p.) through a period ranging from 9 to14 days/ once a day. The rats' estrous cycle was studied using Papanicolaou test; those showing phase of Diestrous were grouped into experimental and control groups. The control group solely received saline (1 ml/kg, i.p.) throughout all experiments. To evaluate the inflammatory effect of NO, the rats were treated an anti-inflammatory agent, naloxone hydrochloride (0.4 mg/kg, i.p.), prior to L-arginine. At the end of the treatment period all animals’ ovaries were assessed for histopathological and histochemical investigations. Also, activation of NO synthase (NOS) in the experiments was studied using NADPH-diaphorase technique. RESULTS: The ovaries of rats treated with L-arginine showed polycystic characteristics in contrast to those collected from control or naloxone pretreated groups, based on image analysis. A difference in enzyme activation was also shown in the sections that belonged to the groups that received L-arginine when compared with the pre-naloxone and control groups. CONCLUSION: Based on these results, we believe that NO may play a major role in the pathophysiology of PCOS.